2006
DOI: 10.1086/505698
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Porosity on X‐Ray Emission‐Line Profiles from Hot‐Star Winds

Abstract: We investigate the degree to which the nearly symmetric form of X-ray emission lines seen in Chandra spectra of early-type supergiant stars could be explained by a possibly porous nature of their spatially structured stellar winds. Such porosity could effectively reduce the bound-free absorption of X-rays emitted by embedded wind shocks, and thus allow a more similar transmission of red-vs. blue-shifted emission from the back vs. front hemispheres. To obtain the localized self-shielding that is central to this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 21 publications
7
158
0
7
Order By: Relevance
“…A toy model for a focussed line-driven wind without clumps (Gies & Bolton 1986b) does not describe the data well and we attribute the differences to the absence of clumping in the model that would lead to the observed strong variations of N H at the same orbital phase. Qualitatively matching the observed N H distributions at a given orbital phase to a toy clumpy wind model (Owocki & Cohen 2006;Sundqvist et al 2012) without a focussed wind and with spherical clumps results in the best match for models with porosity length, h ∞ , on the order of the stellar radius, R * , at orbital phases φ orb ≈ 0.5, in agreement with results from (effectively) single O stars (Leutenegger et al 2013). Our models exclude both much lower and much higher porosities.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A toy model for a focussed line-driven wind without clumps (Gies & Bolton 1986b) does not describe the data well and we attribute the differences to the absence of clumping in the model that would lead to the observed strong variations of N H at the same orbital phase. Qualitatively matching the observed N H distributions at a given orbital phase to a toy clumpy wind model (Owocki & Cohen 2006;Sundqvist et al 2012) without a focussed wind and with spherical clumps results in the best match for models with porosity length, h ∞ , on the order of the stellar radius, R * , at orbital phases φ orb ≈ 0.5, in agreement with results from (effectively) single O stars (Leutenegger et al 2013). Our models exclude both much lower and much higher porosities.…”
Section: Discussionsupporting
confidence: 80%
“…A.2). Based on previous theoretical and observational investigations of single O stars, it is reasonable that h ∞ should be comparable to or smaller than R * (Dessart & Owocki 2003;Owocki & Cohen 2006;Nazé et al 2013). This is also consistent with the results of Leutenegger et al (2013), who found that the spectrum of the single O supergiant ζ Pup could be fit with models having porosity lengths h ∞ ≤ R * .…”
Section: Clumpy Wind Model For the Hard Statesupporting
confidence: 88%
See 1 more Smart Citation
“…Only when the wind-clump collision is almost perpendicular to the line of sight is the radiation observable and spread over a narrow velocity range as derived from the HWHM. The effects of clumping and porosity on X-Ray emission-line profiles from hot-star winds have been described extensively by Owocki & Cohen (2006) and Oskinova et al (2006).…”
mentioning
confidence: 99%
“…The character of the radiation transfer in the wind changes once the clumps become optically thick, because (a) radiation is trapped within the clumps; and (b) channels open up between the clumps that permit radiation from the star to leak out; i.e., the wind becomes "porous". The leakage implied by porosity reduces the effective optical depth of the wind (Owocki & Cohen 2006;Oskinova et al 2007) in a particular transition. Oskinova et al (2007) recognized that resonance transitions become optically thick before other transitions, and consequently a clumped wind could be a porous medium for the P v doublet but not for Hα.…”
Section: The Origin and Nature Of Clumpingmentioning
confidence: 99%